2009
DOI: 10.1089/fpd.2009.0278
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antimicrobial Resistance Transfer Between Lactic Acid Bacteria and Potential Foodborne Pathogens UsingIn VitroMethods and Mating in a Food Matrix

Abstract: The transferability of antimicrobial resistance from lactic acid bacteria (LAB) to potential pathogenic strains was studied using in vitro methods and mating in a food matrix. Five LAB donors containing either erythromycin or tetracycline resistance markers on transferable elements were conjugally mated with LAB (Enterococcus faecalis, Lactococcus lactis) and pathogenic strains (Listeria spp., Salmonella ssp., Staphylococcus aureus, and Escherichia coli). In vitro transfer experiments were carried out with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 48 publications
0
39
0
2
Order By: Relevance
“…Conjugation in food matrices was reported in experimental studies e.g., the transfer of plasmid-borne ampicillin resistance genes from Salmonella Typhimurium to E. coli K12 in inoculated sterilized milk and ground beef [70] and the transfer of antimicrobial resistance from lactic acid bacteria (LAB) ( Enterococcus faecalis , Lactococcus lactis ) to potential pathogenic strains ( Listeria spp., Salmonella spp., Staphylococcus aureus and E. coli ) in fermented whole milk (fermented with the LAB donors) [71]. Van der Auwera et al [72] found significant levels of conjugation and mobilization of plasmids between strains of Bacillus thuringiensis in milk and rice pudding.…”
Section: Antimicrobial Resistance In Foodmentioning
confidence: 99%
See 2 more Smart Citations
“…Conjugation in food matrices was reported in experimental studies e.g., the transfer of plasmid-borne ampicillin resistance genes from Salmonella Typhimurium to E. coli K12 in inoculated sterilized milk and ground beef [70] and the transfer of antimicrobial resistance from lactic acid bacteria (LAB) ( Enterococcus faecalis , Lactococcus lactis ) to potential pathogenic strains ( Listeria spp., Salmonella spp., Staphylococcus aureus and E. coli ) in fermented whole milk (fermented with the LAB donors) [71]. Van der Auwera et al [72] found significant levels of conjugation and mobilization of plasmids between strains of Bacillus thuringiensis in milk and rice pudding.…”
Section: Antimicrobial Resistance In Foodmentioning
confidence: 99%
“…In vitro research showed the transfer of antimicrobial resistance genes by means of conjugation of LAB to Gram-positive and Gram-negative bacteria [13], and among LAB [71], e.g., of tetracycline resistance genes from Lactobacillus plantarum to Lactococcus lactis and Enterococcus faecalis [104], of erythromycin resistance genes from Lactobacillus fermentum and Lactobacillus salivarius , and of tetracycline resistance genes from Lactobacillus plantarum and Lactobacillus brevis to Enterococcus faecalis [105], from Lactobacillus curvatus and Enterococcus faecalis to Lactobacillus curvatus [106], and of tetracycline and erythromycin resistance genes among Enterococcus faecalis isolates [107]. …”
Section: Antimicrobial Resistance In Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Charpentier et al (1999) were able to transfer pIP823 between L. monocytogenes and E. faecalis, and between L. monocytogenes and E. coli. Transfer of antibiotic resistance from lactic acid bacteria to Listeria by conjugation in a food matrix was studied by Toomey et al (2009). They were able to transfer erythromycin resistance in vitro from the lactic acid bacteria to Listeria, but in a food matrix transfer of resistance was seen only between lactic acid bacteria (Toomey et al, 2009).…”
Section: Resistance Mediated By Conjugationmentioning
confidence: 99%
“…In fact, Steidler et al's 20 use of ATCM in L. lactis replacing thyA with a synthetic human IL-10 transgene led to the creation of strain Thy12, which has been validated in pigs, and has been approved by Dutch authorities as an experimental therapy for humans with IBD. recent study, Toomey et al 6 highlighted the involvement of LAB, (Enterococcus faecalis and Lactococcus lactis) as a potential source of resistance determinants that may be disseminated between LAB and pathogenic strains such as E. coli, Listeria spp, Salmonella spp and Staphylococcus aureus. Surprisingly, no resistance transfer was observed with E. coli, Salmonella spp and Staphylococcus aureus; however, erythromycin resistance was transferred by both LAB to Listeria spp.…”
Section: Biocontainment Strategies For Live Lactic Acid Bacteria Vaccmentioning
confidence: 99%